The interleukin-4 expression in patients with severe sepsis - Wu, Huang-Pin; Wu, Chia-Ling; Chen, Chian-Kuang; Chung, Kong; Tseng, Jo-Chi; Liu, Yu-Chih; Chuang, Duen-Yau (Journal of critical care, 2008)
Sepsis is a complicated syndrome in which proinflammatory and anti-inflammatory cytokines are expressed simultaneously. However, it remains unclear for the expression of interleukin (IL)–4 and IL-4 δ2 in patients with severe sepsis. By nested reverse transcriptase–polymerase chain reaction and the expression of glyceraldehydes-3-phosphate dehydrogenase as the internal reference, the expression levels of IL-4 and IL-4 δ2 were determined in peripheral blood mononuclear cells (PBMCs) of 76 patients with severe sepsis and were immediately admitted to an intensive care unit. Plasma IL-4 level was measured by enzyme-linked immunosorbent assay. Clinical characteristics were monitored and recorded prospectively. The IL-4 messenger RNA (mRNA) expression in PBMCs of patients who had survived was significantly higher than that of those who had died. The IL-4 δ2/IL-4 ratio in PBMCs of patients who had survived was significantly lower than that of those who had died. The IL-4 δ2 expression did not differ between survivors and nonsurvivors. After regression analysis, the IL-4 δ2/IL-4 ratio still was an independent factor for death in patients with severe sepsis. The expression of IL-4 δ2 mRNA was positively correlated with that of IL-4 mRNA in patients with severe sepsis. The plasma IL-4 levels in septic patients on admission day did not differ between survivors and nonsurvivors. The IL-4 mRNA expression might be associated with survival in patients with severe sepsis. The IL-4 δ2/IL-4 ratio might be served as the net immunity of IL-4 activity.